Bone Mineral Density in Men - Original Investigation - Duygu Geler Külcü; Burcu Yanık (Galenos Yayinevi, 2007)
Aims: This study is designed to evaluate bone mineral density (BMD) in men who attend to Physical Medicine and Rehabilitation outpatient clinic. Patients and Medhods: 42 men were included into the study. They were evaluated in 3 groups according to their age (30-75); age between 30-45, 45-60 and over 60 yrs. BMD of lumbar spine (L2-L4) and femur neck were evaluated by using dual x-ray absorptiometry (DXA). Serum paratiroid hormone, osteocalcin, 25 (OH) D3 vitamine levels and urinary deoxypridinoline levels were evaluated. Results: Mean age of the patients were 51.24±12.23 yrs in femur neck and in lumbar region, 70% and 15% of the patients between 60-75 yrs, 53% and 7% of the patients between 45-60 yrs and 23% and 8% of the patients between 30-45 yrs have osteoporosis, respectively. Between the groups femur neck BMD and L2-L4 BMD were significantly different (p=0.043 and p=0.008, respectively). Serum PTH levels were high and serum 25(OH)D3 levels were low in all groups. There were no significant difference between the groups regarding bone turnover markers. Seven patients had osteoporotic fractures (6 vertebral, 1 hip). Correlation was found between fractures and L2-L4 BMD ( r=-0.322, p=0.043). Conclusion: Osteoporosis is common also in men, particularly in the middle and old ages. Routine analysis of blood biochemistry and DXA should be performed in adult men. (From the World of Osteoporosis 2007;13:1-5)